1996
DOI: 10.1002/chin.199610222
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Biological Activity 1,2,4‐Triazinotriazinone Derivatives.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The chemistry of polyfunctional 1,2, 4-triazines has proved to be very useful in the synthetic heteropolycyclic nitrogen systems ( Abdel-Rahman et al, 2010;Ibrahim et al, 2009;Ibrahim et al, 2008), as well as established in the field of pharmacological chemistry as anti AIDS and anti-cancer (Abdel-Rahman, 1991;Abdel-Rahman, 1992;Abdel-Rahman, et al, 1994;Abdel-Rahman et al, 1994;Abdel-Rahman et al, 1995;AbdelRahman et al, 1999;El-Gendy et al, 2001;El-Gendy et al, 2003;) and in the plant protection (AbdelRahman R. M., 2001). In additional used their as biocidal targets Abdel-Monem & Abdel-Rahman 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The chemistry of polyfunctional 1,2, 4-triazines has proved to be very useful in the synthetic heteropolycyclic nitrogen systems ( Abdel-Rahman et al, 2010;Ibrahim et al, 2009;Ibrahim et al, 2008), as well as established in the field of pharmacological chemistry as anti AIDS and anti-cancer (Abdel-Rahman, 1991;Abdel-Rahman, 1992;Abdel-Rahman, et al, 1994;Abdel-Rahman et al, 1994;Abdel-Rahman et al, 1995;AbdelRahman et al, 1999;El-Gendy et al, 2001;El-Gendy et al, 2003;) and in the plant protection (AbdelRahman R. M., 2001). In additional used their as biocidal targets Abdel-Monem & Abdel-Rahman 2006).…”
Section: Introductionmentioning
confidence: 97%
“…1,2,4-Triazine derivatives are important classes of heterocyclic compounds which have various biological properties such as anticancer, muscle relaxant, hypnotic, anti-inflammatory, diuretic, and antihypertensive activities [1][2][3][4]. In particular, literature studies on 1,2,4-triazoles have shown that the fused 1,2,4-triazoles have a great potential as antifungal [5], antibactericidal [5,6], anxiolytic [7,8], anticonvulsant [9], or herbicidal [10] activities and can act as "antidepressant" reagents [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BX-1382BS (V) showed a significant activity as protein kinase inhibitor [26] and a cyanopyrimidine scaffold JNJ-17029259 (VI) is an oral inhibitor of VEGF-mediated signal transduction [27] (Figure 1). Recently a great deal of synthetic efforts has been spent on fluorinated uncondensed 1,2,4-triazines by our group searching for new anti-HIV and anticancer agents [28][29][30][31][32][33][34][35][36][37][38] (compounds A-F; Figure 2).…”
Section: Introductionmentioning
confidence: 99%